Community based assessment on knowledge, attitude and practices (KAP), risk factors and One Health perspective of brucellosis in rural and urban settings of Pakistan: A Cross-Sectional Study - Tahir, A; Naz, S; Afzal, M S; Shabbir, R M K; Ali, S; Shah, NA; Ahmed, H (Journal of the Hellenic Veterinary Medical Society, 2022)
Bovine brucellosis is an endemic zoonotic infection of ruminants in Pakistan with detrimental impacts on livestock economy. The major losses caused by brucellosis in animals include abortions, week calves, infertility, and reduced milk production. Regardless of the prevalence of the disease, limited data is available about brucellosis in Pakistan. The present study aimed to access the one health concept in prospective of Brucellosis among small-scale dairy farmers by examining knowledge, attitude and practices at the farms and household level that might pose a risk for humans contracting brucellosis. A community-based cross-sectional survey was conducted among small household dairy farms (n=333) in rural and urban areas of district Rawalpindi and Islamabad. The results revealed almost 74.17% of the participants knew about animal brucellosis and about 69.97% of the participants were able to identify the symptoms of animal brucellosis. 58.26% of participants showed knowledge about the transmission of disease from animals to humans. A majority (70.87%) of participants used the raw milk for making other dairy products. Most household farmers are unaware of routes of transmission and major risk factors of brucellosis. Almost all the participants, except veterinarians, including butchers, dairy farm owners and workers, slaughterhouse owners and workers and farmers were involved in at least one risky practice. The moderate knowledge and poor understanding of the disease emphasize the need to initiate awareness programs to educate the farmers who are at high risk along with the improvement of vaccination programs for animals and strict implementation of brucellosis eradication policy which should be devised by government.